TARBIYA FANINING MAZMUNI VA TARBIYA DARSLARIDA ZAMONAVIY PEDAGOGIK TEXNOLOGIYALARNING O‟RNI - Jumayeva Mohinur Nuftullayeva Shahlo Ergasheva Yulduz (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the essence, importance, methodological foundations, and application of modern pedagogical technologies in teaching the «Tarbiya» subject. It emphasizes the need to implement innovative approaches and enhance the continuous spiritual education processes in the educational system.